Serum Chemerin and Apelin Levels in Obese Children: Relation to Endothelial Function and Inflammation from a Cross-sectional Case–Control Study - Zaki, Moushira E.; ElGebaly, Howida; Hassan, Mona; Elbatrawy, Salwa R.; Yousef, Walaa; Ismail, Ahmed S.; Ahmed, Hanaa Hamdy (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Childhood obesity is a global threat with subsequent health problems among which and most important is cardiovascular problems. It is now claimed that adipokines secreted by adipose tissue are responsible for such consequences. Newly discovered adipokines chemerin and apelin are under investigation for their link with obesity related co-morbidites. AIM: The aim of the present study was to assess the serum levels of chemerin and apelin in obese children and to explore the correlation between these two biomarkers and the inflammatory as well as the endothelial cell activation markers PATIENTS AND METHODS: This study was a cross-sectional case control study that comprised 45 pre-pubertal obese children aged (6– < 12) years old of both sexes (22 males and 23 females), in addition to 45 matched age and sex lean children serving as controls (21 males and 24 females). Serum levels of chemerin, apelin, ICAM-1, E-selectin and hs-CRP were measured for obese and controls. RESULTS: Obese children showed higher levels of chemerin, apelin, ICAM-1 and E-selectin than controls. Chemerin and apelin showed significant correlations with all parameters except for age. Anthropometric parameters with hs-CRP revealed significant correlation even after adjustment for age and sex while apelin only showed a significant correlation with age. Multiple regression analyses with hs -CR , E-selectin and ICAM-1 as dependent variables and BMI Z score ,age, sex, chemerin and apelin as independent variables showed the effect of chemerin and apelin on the increased levels of hs -CR , E-selectin and ICAM-1 . CONCLUSION: Elevated levels of chemerin and apelin may serve as indices of ongoing obesity-related disorders in obese children.